Abu Shouk, Ahmad Ibrahim. “The Science of History: Problems of Methodology and the Islamization Projects,” Year 6, Issue 24 (Spring 1422 AH/ 2001 CE), Pp. 55-87. - أبوشوك, إبراهيم (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2001)
Ahmad Ibrahim Abu Shouk’s article begins by defining “history” as the science that studies the events of the human past and its impacts through a scientific study based on research, validation, verification, observation, inference, and deduction. He then reviews the development of historical research methodologies in Islamic heritage, especially in the thought of al-Ṭabarī, Ibn Miskawayh, al-Bayrūnī, and Ibn Khaldūn. He addresses the development of historical research methodologies in the European West, especially the idealism school of thought, historical materialism, civilizational, and the French "Le Annales" schools of thought. He then discusses the motives of the Islamization of the science of history and its modules, especially in the thought of Emad al-Din Khalil and concludes with expressing the Islamic interpretation of history between Islamization and ta’ṣīl (referral to principal Islamic sources).